2017
DOI: 10.1186/s12891-017-1594-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative electromyographic monitoring to optimize safe lumbar pedicle screw placement – a retrospective analysis

Abstract: BackgroundThe foremost concern of a surgeon during pedicle screw fixation is safety. Assistive modalities, especially intraoperative electromyographic monitoring (EMG) can function as an essential tool to recognize screw malposition that compromise neural integrity, so that the screws can be repositioned immediately rather than later. We intend to study the efficacy of intraoperative EMG monitoring to detect potential pedicle breach and evaluate whether reoperation rates were significantly reduced.MethodsRetro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
1
18
0
2
Order By: Relevance
“…With the advent of neuromonitoring, intra-operative assessment of potential pedicle breaches that can compromise neurological integrity has improved [ 10 , 40 , 41 ]. In combination with fluoroscopy, neuromonitoring has become a valuable tool to identify such breaches [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of neuromonitoring, intra-operative assessment of potential pedicle breaches that can compromise neurological integrity has improved [ 10 , 40 , 41 ]. In combination with fluoroscopy, neuromonitoring has become a valuable tool to identify such breaches [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has become a common procedure, and in-spite of spine surgeons being proficient with the technique, malpositioning of pedicle screws can still occur [ 8 , 9 ]. Such malpositioning not only compromises the stability of the construct but also endangers neural integrity [ 10 ]. Various authors have reported different rates of pedicle breach ranging between 1.7% to 35% during open pedicle screw placement and 2.6% to 12.3% during minimally invasive pedicle screw placement [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…One such study, which was conducted in the abdominal and leg muscles of sheep, showed that EMG could be effectively used to indicate the pedicle screw position [2]. EMG has been utilized as a technique to facilitate accurate pedicle screw placement for both the thoracic and lumbar spine [2,4], and its ability to detect breaches in the pedicle cortex is advantageous to imaging techniques during minimally invasive procedures [14]. However, lateral pedicle breaches are difficult to identify using EMG alone [14].…”
Section: Drawbacks To the Use Of Emg Alone During Screw Placementmentioning
confidence: 99%
“…The current study suggests a novel method to improve neuromonitoring during pedicle screw placement using the transabdominal motor action potential (TaMAP) technique. This neurophysiological tool can assess the functional integrity of individual nerve roots in real-time and may help surgeons recognize impending neural injuries that cannot be detected by traditionally used techniques such as electromyography (EMG) [4]. Back pain is one of the most common conditions worldwide, suggested to affect 80% of adults during their lifetime; thus, safely monitoring screw placement for treating back pathologies is of crucial importance [5].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…IONM during spinal surgery utilizes three different modalities, namely, somatosensory evoked potential (SSEP), motor evoked potential (MEP), and electromyography (EMG) [10][11][12]. In view of the devastating consequences of a neurological injury, many surgeons advocate the routine use of IONM to detect possible intraoperative insult; hence immediate remedial measures can be taken [13].…”
Section: Introductionmentioning
confidence: 99%